2014
DOI: 10.1111/liv.12517
|View full text |Cite
|
Sign up to set email alerts
|

miR‐181a mediates TGF‐β‐induced hepatocyte EMT and is dysregulated in cirrhosis and hepatocellular cancer

Abstract: MiR-181a had a direct effect in inducing hepatocyte EMT and was able to replace TGF-β-induced effects in vitro. MiR-181a was over-expressed in cirrhosis and HCC and is likely to play a role in disease pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 38 publications
1
58
0
Order By: Relevance
“…MicroRNAs are critical to both physiological and pathological processes, including tumor development and progression [7,9,25]. Some miRNAs have even been identified as cancer markers or prognostic markers for cancer patients [9,10,26].…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs are critical to both physiological and pathological processes, including tumor development and progression [7,9,25]. Some miRNAs have even been identified as cancer markers or prognostic markers for cancer patients [9,10,26].…”
Section: Discussionmentioning
confidence: 99%
“…HCC develops predominantly in an established background of chronic liver diseases mainly caused by persistent infection of hepatitis B [4] and/or hepatitis C virus, alcoholic liver disease, or non-alcoholic steatohepatitis [5,6]. Meanwhile, growing evidence indicates that the epithelial-mesenchymal transition (EMT), a developmental process by which epithelial cells reduce intercellular adhesions and acquire fibroblastoid properties, has important roles in the acquisition of the invasive and metastatic potentials of cancer progression [7,8,9,10]. We have recently reported that sorafenib [11,12] exerts a potent inhibitory activity against the EMT by inhibiting MAPK signaling and SNAI1 expression in HCC [13].…”
Section: Introductionmentioning
confidence: 99%
“…As in glioblastoma, significant downregulation of hsa-miR-181a was also observed in squamous lung cell carcinoma,83 oral squamous cell carcinoma,71 luminal A-like breast cancer,67 and non-small-cell lung cancer 84. However, hsa-miR-181a was significantly overexpressed in MCF-7 breast cancer cells,85 colorectal cancer,28 and hepatocellular carcinoma cells 56,86,87. Hsa-miR-181a was upregulated in acute myeloid leukemia,76 especially in the M1 and M2 subtypes, and in myelodysplastic syndromes88 but downregulated in multiple myeloma89 and chronic lymphocyte leukemia 79,90.…”
Section: Discussionmentioning
confidence: 92%
“…Thus, tissue-specific miRNAs may be used as effective biomarkers for cancer diagnosis, treatment, and prognosis 8. Hsa-miR-181a has been proposed to play a role in the pathogenesis, development, progression, metastasis, prognosis, and therapeutic response to chemo- and radiotherapy in EC,4,53 ovarian cancer,54 glioma,30,55 liver cancer,56 colorectal cancer,5759 gastric cancer,60,61 lung cancer,62 breast cancer,6367 cervical carcinoma,68,69 pancreatic cancer,46 osteosarcoma,70 oral squamous cell carcinoma,71,72 B-cell lymphoma,73 thyroid cancer,74 salivary adenoid cystic carcinoma,75 and acute and chronic leukemias 7681. Ciafrè et al,82 firstly reported that the expression of hsa-miR-181a was significantly downregulated in primary glioblastomas and human glioblastoma cell lines compared with normal brain tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation